PENGGUNAAN BAHASA TRANSMIGRAN JAWA DI KABUPATEN GORONTALO - Sayama Malabar (Humaniora, 2012)
The  Javanese Trans migrants have come to Gorontalo district since 1953. The language used by the Trans migrants continued to be used in the place so that it becomes bilingual and even multilingual community giving rise to new phenomena. The aim of this study Is to identify pattern of language usage in family, market, school, mosque, and the office; and variation of language choice. The research methodology used comprised observation method including basic recording technique, interview methodology elevation basic technique, survey method by distributing questionnaires, triangulation techniques, and sociolinguistic approach. The sample is determined by snowball and purposive sampling. Data analyzed using SPEAKING through percentage calculation. The result show that The Javanese trans migrants to Gorontalo District is dominant of lndonesian language use in the office, mosque, and school; Javanese in family and market; Malay language in school, and market; and three types of language variations, single language variation, code switching, and mixing.  Single language variation involves Javanese and Indonesian. Code switching is divided into four variations and mixing code is split in two variations.  So that, the use of trans migrants language in Gorontalo is dominant in Indonesian and Javanese pattern simultaneously.